2018
DOI: 10.1177/1932296818776993
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glucose Variability With Glucose-Dependent Versus Glucose-Independent Therapies Despite Similar Glucose Control and Hypoglycemia Rates in a Randomized, Controlled Study of Older Patients With Type 2 Diabetes Mellitus

Abstract: This CGM substudy in older patients with T2DM showed lower within- and between-day BG variability with glucose-dependent therapies but similar HbA1c reductions and hypoglycemia duration with glucose-independent strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…53 Similarly, CGM proved to be useful for investigating hypoglycemia and glycemic variability in the IMPERIUM study performed in moderately ill and/or frail older (≥65 years) individuals with inadequately controlled T2DM. 54 In the MOBILE RCT comparing CGM to SMBG in adults with T2DM treated with basal insulin without prandial or bolus insulin, improvement in key glycemic outcomes, including time-in-range and less time in hyperglycemia, was observed with CGM compared with SMBG in participants ≥65 years old (mean ± standard deviation age of 69±4 years), and was comparable with the treatment outcomes observed in younger participants. 55 A recent analysis of a heterogeneous non-critically ill inpatient population with diabetes on insulin therapy demonstrated good overall accuracy of CGM, even in the presence of comorbidities such as impaired renal function, cardiovascular and respiratory illnesses, and mild-to-moderate anemia.…”
Section: Dovepress 1697mentioning
confidence: 71%
“…53 Similarly, CGM proved to be useful for investigating hypoglycemia and glycemic variability in the IMPERIUM study performed in moderately ill and/or frail older (≥65 years) individuals with inadequately controlled T2DM. 54 In the MOBILE RCT comparing CGM to SMBG in adults with T2DM treated with basal insulin without prandial or bolus insulin, improvement in key glycemic outcomes, including time-in-range and less time in hyperglycemia, was observed with CGM compared with SMBG in participants ≥65 years old (mean ± standard deviation age of 69±4 years), and was comparable with the treatment outcomes observed in younger participants. 55 A recent analysis of a heterogeneous non-critically ill inpatient population with diabetes on insulin therapy demonstrated good overall accuracy of CGM, even in the presence of comorbidities such as impaired renal function, cardiovascular and respiratory illnesses, and mild-to-moderate anemia.…”
Section: Dovepress 1697mentioning
confidence: 71%
“…Moreover, the potential influences of antidiabetic treatments and concurrent medications on the association between HbA1c variability and DR in T2DM patients are unknown, which should be evaluated in future studies. For example, a previous study suggested that glucose-dependent therapies may be associated with lower within- and between-day glucose variability but similar HbA1c reductions and hypoglycemia duration as compared to glucose-independent strategies in old patients with T2DM 46 . In addition, several clinical studies have also suggested that sitagliptin 47 48 or dulaglutide 49 may be more effective than sulfonylureas in improving the glucose fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…therapies may be associated with lower within-and between-day glucose variability but similar HbA1c reductions and hypoglycemia duration as compared to glucose-independent strategies in old patients with T2DM [46]. In addition, several clinical studies have also suggested that sitagliptin [47,48] or dulaglutide [49] may be more effective than sulfonylureas in improving the glucose fluctuation.…”
Section: Continuedmentioning
confidence: 99%
“…10 Studies have reported that patients with T2DM should not only reduce HbA1c to target levels, but also need to control GV to avoid hypoglycaemia and extensive postprandial glycaemic excursions. 11,12 A prospective cohort study showed that an increased CV was associated with the risk of all-cause mortality in patients with T2DM who had a well-controlled glucose status at long-term follow-up. 13 Therefore, CV serves as an important outcome indicator in clinical trials of CGM, and clarifying the factors that determine CV is essential for the management of T2DM and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that patients with T2DM should not only reduce HbA1c to target levels, but also need to control GV to avoid hypoglycaemia and extensive postprandial glycaemic excursions 11,12 . A prospective cohort study showed that an increased CV was associated with the risk of all‐cause mortality in patients with T2DM who had a well‐controlled glucose status at long‐term follow‐up 13 .…”
Section: Introductionmentioning
confidence: 99%